ANALISIS KUALITAS PERAIRAN BUDIDAYA RUMPUT LAUT DI DUSUN SALIONG DESA BATU BOY SEBAGAI DAMPAK GAGAL PANEN - Zakariah, Muhammad Ikbal; Koto, Saifuddin; Irsan, Irsan; Fesanrey, Wilda (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: The production of seaweed cultivation in Saliong Hamlet, Batu Boy Village, hasdecreased, and there have even been crop failures in the last five years. For this reason, an analysisof the factors suspected of influencing the failure is needed. The purpose of this study was to analyzethe quality of seaweed cultivation waters in Saliong Hamlet, Batu Boy Village by using physicalchemical factors of the waters.Methods: There are three stations used for sampling. The physical and chemical parameters of thewaters measured include temperature, brightness, current speed, water depth, pH, salinity, TDS,DO, BOD, phosphate, heavy metal mercury (Hg) and cyanide. To determine water quality, the resultsof measuring physical-chemical water parameters will be compared with sea water quality standardsfor marine biota and quality standards for seaweed cultivation based on experts in the field.Results: The research results showed that temperature, depth, TDS, phosphate and heavy metalmercury did not meet quality standards. While the parameters of brightness, turbidity, currentvelocity, pH, salinity, DO, BOD and cyanide are still in accordance with the quality standards forseaweed cultivation.Conclusion: The quality of the waters in the seaweed cultivation area in Saliong Hamlet still meetsthe quality standards and some does not comply with the quality standards. The occurrence ofseaweed harvest failure can be caused by the presence of physical-chemical factors in the watersthat are less supportive.